2019
DOI: 10.4103/ijmbs.ijmbs_73_18
|View full text |Cite
|
Sign up to set email alerts
|

Poor quality of sleep in patients on chronic hemodialysis

Abstract: Patients with chronic renal disease, and in particular chronic hemodialysis patients, are prone to various sleep disorders (SDs) that may affect their daily quality of life and contribute to increased their cardiovascular morbidity and mortality. [1] In comparison to the general population, the prevalence of SDs in patients with renal impairment is significantly increased due to the presence of usual risk factors such as age, gender, obesity and other factors specific to uremia and dialysis (anemia, uremic tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
2
3
0
2
Order By: Relevance
“…In the present study, patients with diabetes mellitus had significantly ( P < 0.05) poor nighttime sleep. Similar results were reported with a lower quality of sleep in patients with diabetes mellitus undergoing MHD 26,33,34 . Night sleep quality was reported significantly poor among patients who did not complain of numbness ( P < 0.05) This was in contrast to findings in which nighttime sleep quality was significantly poor due to symptoms such as itching, tingling and numbness in the patients 35 …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In the present study, patients with diabetes mellitus had significantly ( P < 0.05) poor nighttime sleep. Similar results were reported with a lower quality of sleep in patients with diabetes mellitus undergoing MHD 26,33,34 . Night sleep quality was reported significantly poor among patients who did not complain of numbness ( P < 0.05) This was in contrast to findings in which nighttime sleep quality was significantly poor due to symptoms such as itching, tingling and numbness in the patients 35 …”
Section: Discussionsupporting
confidence: 78%
“…The current study showed no significant association of interdialytic weight gain, hemoglobin, and albumin with sleep quality (daytime sleepiness and nighttime sleep). In another study, they have also reported similar results where sleep quality did not have any significant association with serum Hb, albumin, and intradialytic weight gain 34 . This study reported that consumption of diuretic drugs had no association with daytime sleepiness and nighttime sleep.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Poor sleep is linked to an increased risk of hypertension, progressive CKD, impaired glucose tolerance, diabetes mellitus, depression, and greater use of medical services ( 16 ). If left untreated, these conditions are also more likely to result in heart disease and a higher mortality rate ( 17 , 18 ). Sedative medicines are the first line of treatment for sleep disruption in these individuals ( 19 ).…”
mentioning
confidence: 99%